Estimating nesting habitat characteristics for the Kentish plover (Anarhynchus alexandrinus) with the effect of substrate and vegetation using a Bayesian network approach - Dong-Yun Lee; Ju-Hyun Lee; Jong-Ju Son; Seung-Jun Oh; Ha-Cheol Sung (PLoS ONE, 2025)
Coastal habitats play an important role in the nesting ecology of shorebirds; however, these habitats are increasingly threatened by human activity and ongoing habitat loss. The conservation of shorebird populations thus necessitates understanding the utilization pattern of artificial coastal habitats by these birds. Substrate particle size and vegetation cover are key environmental factors influencing the nest site selection and nest success in ground-nesting shorebirds such as plovers. This study aimed to investigate the impact of substrate particle size and vegetation cover for the Kentish plover (Anarhynchus alexandrinus) nesting sites within an artificial coastal environment, the Saemangeum reclaimed land. Geological criteria and 1-m2 quadrat photos were used to develop Bayesian network (BN) models to analyze the impact of these variables on nest site selection and nest success in 2020. The BN models predicted the impact of substrate particle size and vegetation cover on the likelihood of nest presence and nest success. The results indicated that Kentish plovers prefer sandy sites with moderate vegetation cover and achieve higher nest success in habitats with mixed soil types, including medium (0.25–0.5 mm), fine (0.125–0.25 mm), and very fine (0.063–0.125 mm) sand, along with small proportions of mud (<0.063 mm). These findings highlight the importance of evaluating the complex interactions between plover nests and substrate characteristics, including soil porosity and permeability. Vegetation cover must also be managed with attention to the trade-offs involved, such as predation risk, nest camouflage, crypsis, and thermoregulation which influence plover nesting preference and success. This study provides valuable quantitative insights and emphasizes the need for incorporating multi-layered ecological factors along with inherent uncertainties in coastal environments to restore appropriate artificial coastal habitats for shorebird conservation.